2018
DOI: 10.1093/ageing/afy125
|View full text |Cite
|
Sign up to set email alerts
|

Parental longevity predicts healthy ageing among women

Abstract: parental longevity predicted healthy ageing in a national cohort of postmenopausal women, supporting the view that genetic, environmental, and behavioral factors transmitted across generations may influence ageing outcomes among offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 30 publications
(66 reference statements)
2
20
0
Order By: Relevance
“…Several previous studies have found that individuals with long-lived parents tend to age healthier [3,29]. Parental longevity influences aging not only because of genetics, but also because of shared lifestyle and environmental factors [3]. Results from a recent study from the Women's Health Initiative found that having a mother that achieved HA correlated with HA in postmenopausal women (OR, 1.25; 95% CI, 1.11-1.42) [3].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Several previous studies have found that individuals with long-lived parents tend to age healthier [3,29]. Parental longevity influences aging not only because of genetics, but also because of shared lifestyle and environmental factors [3]. Results from a recent study from the Women's Health Initiative found that having a mother that achieved HA correlated with HA in postmenopausal women (OR, 1.25; 95% CI, 1.11-1.42) [3].…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies have found that individuals with long-lived parents tend to age healthier [3,29]. Parental longevity influences aging not only because of genetics, but also because of shared lifestyle and environmental factors [3].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations